1999
DOI: 10.1080/095851999340198
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits discriminating between employees in public- and in private-sector organizations

Abstract: Based on data collected from public and private organizations in Greece, this paper examines the differences in individual traits between public and private-sector employees, differences which eventually in uence employees' attitudes and behaviours towards their organizations and their consequent performance, speci cally in organizational commitment and neglect behaviour. The ndings indicate that there are some differences between the two groups of employees. In only three out of ten personality characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 54 publications
2
36
0
4
Order By: Relevance
“…Although most research has suggested no differences between the sectors in security and pay needs (Bourantas & Papalexandris, 1999), as well as general motivation (Baldwin, 1987), other research has suggested that government managers have lower levels of motivation as compared to their private sector counterparts (Rainey, 1979). Overall, it appears that there are no major differences in job satisfaction and motivation between the sectors, but more research may be warranted to clear up some discrepancies.…”
Section: Proposed Theoretical Differencesmentioning
confidence: 87%
See 3 more Smart Citations
“…Although most research has suggested no differences between the sectors in security and pay needs (Bourantas & Papalexandris, 1999), as well as general motivation (Baldwin, 1987), other research has suggested that government managers have lower levels of motivation as compared to their private sector counterparts (Rainey, 1979). Overall, it appears that there are no major differences in job satisfaction and motivation between the sectors, but more research may be warranted to clear up some discrepancies.…”
Section: Proposed Theoretical Differencesmentioning
confidence: 87%
“…Employees within the public sector have perceived lower goal clarity in their jobs (Baldwin, 1987) yet have also displayed a lower need for clarity in the first place (Bourantas & Papalexandris, 1999). However, some research suggests that there are no differences in role conflict or ambiguity between sectors (Rainey, 1979), proposing that the vagueness of public sector objectives may not actually lead to role ambiguity or role conflict.…”
Section: Proposed Theoretical Differencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Empirical research shows that, in general, the satisfaction levels of private organization employees are significantly higher than those of public employees (Buchanan, 1975;Bourantas and Papalexandris, 1999;Buka and Bilgic 2012, p. 234). This is also supported by the results study of Bordia and Blau (1998), which proved that pay satisfaction increases the overall job satisfaction, but public employees have less room for managing their pay levels.…”
Section: Reward System and Recognitionmentioning
confidence: 99%